2018
DOI: 10.2903/j.efsa.2018.5280
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetically modified maize 4114 for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2014‐123)

Abstract: Maize 4114 was developed through Agrobacterium tumefaciens-mediated transformation to provide protection against certain lepidopteran and coleopteran pests by expression of the Cry1F, Cry34Ab1 and Cry35Ab1 proteins derived from Bacillus thuringiensis, and tolerance to the herbicidal active ingredient glufosinate-ammonium by expression of the PAT protein derived from Streptomyces viridochromogenes. The molecular characterisation data did not identify issues requiring assessment for food/feed safety. None of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The updated bioinformatics analyses of events DP4114, MON 810, MIR604 and NK603 confirm the assessments provided in the context of previous Scientific Opinions (EFSA GMO Panel, 2018a, 2019b, 2021a,f).…”
Section: Assessmentsupporting
confidence: 74%
See 1 more Smart Citation
“…The updated bioinformatics analyses of events DP4114, MON 810, MIR604 and NK603 confirm the assessments provided in the context of previous Scientific Opinions (EFSA GMO Panel, 2018a, 2019b, 2021a,f).…”
Section: Assessmentsupporting
confidence: 74%
“…The GMO Panel had previously concluded that these studies are in line with Regulation (EU) No 503/2013 and do not show adverse effects related to diets incorporating the single‐event maize DP4114 (EFSA GMO Panel, 2018a), MON 810 or NK603 (EFSA GMO Panel, 2021a).…”
Section: Assessmentmentioning
confidence: 80%
“…The GMO Panel had previously concluded that these studies are in line with Regulation (EU) No 503/2013 and do not show adverse effects related to diets incorporating the single‐event maize DP4114 (EFSA GMO Panel, 2018b), MON 89034 (EFSA GMO Panel, 2019e), MON 87411 (EFSA GMO Panel, 2018c) and DAS‐40278‐9 (EFSA GMO Panel, 2021c).…”
Section: Assessmentmentioning
confidence: 76%
“…Human and animal dietary exposure assessment to DvSnf7 dsRNA and its derived siRNAs was not conducted because these molecules are generally rapidly denaturated, depurinated and degraded shortly after ingestion, and therefore, they are considered generally not to exert any biological effects once ingested by humans and animals (EFSA GMO Panel, 2018b).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation